PELATIHAN PEMBUKUAN SEDERHANA DAN LITERASI INTERNET PADA GURU DAN SISWA SEKOLAH DASAR NEGERI LENGKONG 2 DI DUSUN BANJAR MELATI DESA LENGKONG, KABUPATEN MOJOKERTO - Dodik Juliardi; Triadi Agung udarto (CV. AGUSPATI RESEARCH INSTITUTA, 2022)
This PKM activity aims to help teachers and student of SDN Lengkong 2. In addition, they provided training to students of elemtary school and employees to increase their knowledge about simple bookkeeping and Internet Literacy. Base on the situation analysis it can be inferres that there were several problems surrounding. The problems are lack of facilities and infrastructures , the lack of simple Bookeeping, lack of internet literacy and the knowledge about computer. The method of implementing the activity is by providing the training simple bookkeeping and internet Literacy. The results of this training activity can increase the use of knowledge of bookkeeping, computers and the internet when studying at SDN Lengkong 2 to support skills when working, so that later not only as factory workers and farmers, but also as a provision to open a small business that will improve the quality of life. their income.